Transcriptome analysis of 3D4/21 cells expressing CSFV NS4B - Dong, Wang; Lv, Huifang; Song, Yuzhen; Lv, Yujin; Xu, Xiapeng; Jing, Huiyuan; Peng, Zhifeng; Song, Xinghui; Guo, Yongbin (Frontiers in Microbiology, 2025)
Classical swine fever (CSF) caused by classical swine fever virus (CSFV) has resulted in severe losses to the pig industry worldwide. CSFV non-structural protein 4B (NS4B) plays a crucial role in CSFV replication and pathogenicity. However, the function of NS4B is still limited during CSFV infection. In this study, the RNA-seq was used to investigate differentially expressed genes (DEGs) in 3D4/21 cells expressing CSFV NS4B. 4397 DEGs were identified in 3D4/21 cells expressing NS4B compared to cells expressing the empty vector (NC). Twelve DEGs were selected and further verified by RT-qPCR. Enrichment analyses of GO annotations and KEGG pathways revealed that these DEGs were associated with endocytosis, autophagy, cell adhesion, transport, immune response, apoptosis and so on. The expression of endocytosis-related genes, including CAV1/2, CAVIN2, Rab1B, CHMP2B/4C, VPS35, SNX2, Rab11B, CHMP6, MVB12B and VPS28, were found to be regulated. In addition, some genes associated with host immune defense, such as USP15, DHX29, DDX3, RIG-I and MDA5, were downregulated and the genes associated with host autophagy, such as WIPI2, ATG16L2, SMCR8, RPTOR and MLST8, were upregulated. Therefore, CSFV NS4B involved in virus invasion and intracellular trafficking, the induction of autophagy and the inhibition of antiviral response. Taken together, this study provides useful information for further understanding the function of NS4B during CSFV infection.